KETERLIBATAN MASYARAKAT DALAM PENGELOLAAN SAMPAH DI KOTA CIREBON - Dwi Setyaningsih; Teguh Yuwono; Neny Marlina (Journal of Politic and Government Studies, 2017)
Waste is solid remain of human activities and is abundant in major cities. If not managed well, waste will become a problem and causes many risks and dangers for public welfare, such as causing floor, creating unhealthy environment, disturbing city scenery, and even creating social problems. So, correct waste management is required. Waste management in Cirebon still uses collect – transport – dispose pattern, leading to low community involvement in waste management. Community involvement in waste management is important considering the volume of waste increases every day while the government doesn’t have enough budgets to use advanced technology in waste management.This study was performed by combined method of qualitative and descriptive quantitative researches using interview, observation, documentation and questionnaire data to describe the actual condition, as well as using triangulation of data source, technique, and theory.The research result showed that waste management in Cirebon still usescollect – transport – dispose patternan hasn’t worked with private sector or NGO. Community involvement in waste management was quite good in packing, collecting, and transporting, while the involvement in the implementation of 3Rwas lacking. Government efforts to improve community involvement were socialization and coaching.Keywords: Waste, Waste Management, Community Involvement